The Effect of Compensation, Work Motivation and Work Discipline on the Performance of PT. Khong Guan - Sulaeman, Ahmad Fauzi; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This research aimed to analyze the impact of compensation factors, work motivation, and work discipline on employee performance through quantitative methods, employing primary data from 141 distributed questionnaires. The study employed descriptive and inferential analyses, encompassing instrument test analysis, model feasibility test, multiple linear regression correlation analysis, and hypothesis tests. The regression analysis revealed a positive influence on performance, as indicated by the equation Performance = 0.361 K + 0.226 M.K + 0.273 D.K. The feasibility test affirmed the model's significance (p-value = 0.000), signifying that all independent variables significantly influence performance. Hypothesis testing demonstrated significant values for compensation (0.000), work motivation (0.002), and work discipline (0.000), supporting the acceptance of hypotheses. Management is advised to prioritize the compensation factor with the greatest contribution to PT Khong Guan employees' performance. Addressing employees' perceptions and fostering motivation and discipline can enhance overall company goals. Including a sentence about potential areas for future research based on the findings would provide a forward-looking perspective.